Evaluation of Library Programs in Increasing Reading Interest Students at MI Plus Nur Rahma Bengkulu City - Afindi, Afindi; Tanjua, Atik Likai (Al-Khair Journal: Management Education, 2025)
Abstrac: Reading interest among students is still relatively low, as evidenced by the library program being positioned merely as a complement and not being empowered or made effective. This study aims to evaluate the effectiveness of the library program in increasing students’ reading interest at MI Plus Nur Rahma, Bengkulu City. It uses a descriptive qualitative method with the CIPP evaluation model approach (context, input, process, and product). Data collection techniques include observation, interviews, and documentation. The results of the study show that the contextual aspect of the library program emerged as a response to students’ low literacy culture and the need to strengthen reading habits within the school environment. In terms of program input, the school has provided basic facilities such as a library room and a book collection, and has involved teachers and librarians, although the number and variety of books are still limited and the human resources need improved competencies. In the program process aspect, the implementation has been carried out regularly and in a structured manner through various literacy activities, although coordination and evaluation are still not optimal. Meanwhile, in the product aspect, the program has shown results in the form of increased reading frequency and students’ enthusiasm for literacy activities, although the improvement is not evenly distributed across all classes. Thus, the library program can enhance students’ reading interest. Therefore, it is recommended that to further improve students’ reading interest, the evaluation of the library program in the madrasa should be strengthened.Keywords: Library Program Evaluation, Students’ Reading Interest. Abstrak: Minat baca dikalangan siswa masih tergolong rendah terlihat program perpustakaan masih diposisikan sebagai pelengkap dan tidak diberdayakan serta tidak berdaya guna. Penelitian ini bertujuan untuk mengevaluasi efektivitas program perpustakaan dalam meningkatkan minat baca siswa di MI Plus Nur Rahma Kota Bengkulu. Menggunakan metode kualitatif deskriptif dengan pendekatan model evaluasi CIPP (context, input, process, dan product). Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa aspek konteks program perpustakaan lahir sebagai respons terhadap rendahnya budaya literasi siswa serta kebutuhan penguatan pembiasaan membaca di lingkungan sekolah. Aspek input program, sekolah telah menyediakan fasilitas dasar seperti ruang perpustakaan dan koleksi buku, serta melibatkan guru dan pustakawan, meskipun jumlah dan variasi buku masih terbatas dan sumber daya manusia perlu ditingkatkan kompetensinya. Aspek proses program, pelaksanaan program telah berjalan secara rutin dan terstruktur melalui berbagai kegiatan literasi, namun koordinasi dan evaluasi masih belum optimal. Sedangkan aspek produk, program telah menunjukkan hasil berupa meningkatnya frekuensi membaca dan antusiasme siswa terhadap kegiatan literasi, meskipun belum merata di semua kelas. Dengan demikian, dapat disimpulkan bahwa program perpustakaan dapat meningkatkan minat baca siswa. Sehingga dapat disarankan, jika ingin meningkatkan minat baca siswa, maka tingkatkan evaluasi program perpustakaan di madarasah.Kata kunci: Evaluasi Program perpustakaan, Minat Baca Siswa.